2013
DOI: 10.1007/s11325-013-0886-4
|View full text |Cite
|
Sign up to set email alerts
|

Retention of mandibular advancement devices in the treatment of obstructive sleep apnea: an in vitro pilot study

Abstract: PurposeIn order for a mandibular advancement device (MAD) to be efficacious, it must remain seated on the teeth during sleep. Quantitative data on the retentive characteristics of MADs are currently unavailable. The present pilot study is the first to describe an in vitro setup testing the retentive characteristics of different monobloc MADs.MethodsA hydraulic cyclic test machine was used with MADs seated on dental casts to measure retention forces upon removal of the MADs. A custom-made monobloc (CM-mono), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The setup used in this study extends the experimental setup used previously 8 by introducing a more standardized set of carriers with respect to tooth anatomy and shape of the tooth arcs. The results indicate that the measurements did not differ significantly between the two types of carriers, namely epoxified casts versus ANA-4 Frasaco models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The setup used in this study extends the experimental setup used previously 8 by introducing a more standardized set of carriers with respect to tooth anatomy and shape of the tooth arcs. The results indicate that the measurements did not differ significantly between the two types of carriers, namely epoxified casts versus ANA-4 Frasaco models.…”
Section: Discussionmentioning
confidence: 99%
“…The casts and ANA-4 models were mounted in average value inclination of the occlusal plane and centred in a hydraulic cyclic test machine (Dartec HC10, Testbench Dartec 9600 Controller; Dartec, UK) as described previously 8 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to assess the state of dental support, rendered sensitive by the phenomena of apposition and resorption inevitably induced by displacing teeth 32 , and to ensure absence of mobility.…”
Section: Periodontal Assessmentmentioning
confidence: 99%
“…A previous randomized cross-over trial found that a monobloc nonadjustable thermoplastic MAD with insufficient overnight retention was less effective that a custom-made MAD [13]. The main requirement for a MAD to be effective is the adequate retention on the teeth while the patient is asleep [14,15]. The aim of this study was to evaluate the efficacy of a titrable, thermoplastic MAD compared to a custommade MAD for mild to severe OSA therapy.…”
Section: Introductionmentioning
confidence: 99%